Verbal and Non-Verbal Markers of Root Modality in EU Maritime Affairs and Fisheries vs. Agriculture and Rural Development Reports and Studies: An Overview - Molina-Plaza, Silvia (Kalbotyra, 2015)
This paper examines different options used by writers in reports and studies to control information from two departments of the European Commission: EU Maritime Affairs and Fisheries and Agriculture and Rural Development, using the web as corpus. These two Directorates or Commissions have the power of initiative, are responsible for policy formulation and policy implementation. Two comparable sub-corpora of reports and studies have been selected from the two Directorates. Fifteen markers related to key areas of root modal expression are presented: modal-evaluative adjectives like essential, necessary, suitable and appropriate (Van linden 2012); the semi- modals (e.g. have to, be able to, be supposed to, need to) (Leech et al. 2009); the emerging modal want to (Verplaetse 2010) and expressions with comparative adverbs (e.g. had better, would rather) (van der Auwera et al. 2013). The study of these markers reveals that shared norms and action in these two EU areas are constantly collectively established. Root modals are one of the rhetorical strategies of legitimization and persuasion used in EU’s political discourse by the different parties involved.